The LITERACY-Portal as the Subject of a Case Study on a Human-Centered Design Solution Supporting Users with Special Needs - Hagelkruys, Dominik; Motschnig, Renate (International journal on e-learning, 2017)
Case studies help to reflect and to capture information about complex processes and domains and to make it reusable for future application in related contexts. In the case study reported in this article, we aim to capture and share processes and experience that we gained while designing a web-portal for supporting the specific user group of dyslexic youths and adults. The subject of research is the LITERACY-project. The LITERACY-project is an on-going European wide research project aimed at the social inclusion of dyslexic users by the means of ICT. The article discusses the specific design steps taken to create a portal that fits the needs of its targeted user-group as well as methods and strategies to include users into the design process. Furthermore the article addresses and analyzes specific measures and functionalities provided by the portal that are targeted at the social inclusion of people with dyslexia.